Approaches to ensuring proper working conditions using sensor technologies IoT - Khalimonov, Y.; Sezonova, I.; Sotnik, S. (Вид-во Іванченка І. С., 2024)
The work examines features of introduction of IoT sensor technologies to ensure appropriate conditions in production environment. Modern approaches to creation of integrated monitoring systems that allow to control key parameters of production process: from air quality to level of energy consumption are considered. A detailed analysis of existing constraints in implementation of such systems, including technological, infrastructural and economic aspects, is presented. Particular attention is paid to integration of different types of sensors into single network and ensuring reliable data transmission. A systematic approach to assessing and overcoming identified limitations has been proposed, which allows optimizing process of implementing IoT solutions in production. The presented results are of practical importance for modernization of industrial facilities and development of new systems for monitoring working conditions.
Keywords: sensor technology; industrial IoT; monitoring of production conditions; occupational safety; energy efficiency